Age-related differences in balance, gait, and dual-task costs: A cross-sectional study. - Goulets, Daria; O'Neil, Jennifer; Sheehy, Lisa (Clinical Biomechanics, 2026)
Dual-tasking is essential for daily activities, demanding the coordination of cognitive and physical functions which often decline with age. These declines can adversely affect gait and balance, increasing fall risks in older adults. However, there is little research on how aging is associated with gait under dual-task conditions and on the relationship between balance and dual-task gait. This study aimed to investigate age-related differences in spatiotemporal gait parameters during dual-tasking, and the related dual-task costs, and to explore the relationship between balance and gait performance in younger and older adults. A cross-sectional study was conducted with 15 younger adults (mean age 21) and 15 older adults (mean age 76). Participants completed a balance assessment using a force plate. Gait and dual-task performance were evaluated using the Timed Up and Go (TUG) test on a pressure-sensing walkway, under single-task, dual-task (manual), and dual-task (cognitive) conditions. Statistical analyses included descriptive statistics, linear mixed models, and Pearson's correlations. Older adults exhibited increased TUG times and velocity, and shorter stride length than younger adults across both TUG dual-task conditions. Dual-tasking increased TUG times and decreased velocity and cadence for both age groups. However, dual-task costs were not significantly associated with age group, and weak to moderate (non-significant) correlations were found between static balance and dynamic spatiotemporal gait parameters. Older age is associated with gait and balance disturbances, including under dual-task conditions. This underscores the need for targeted interventions to enhance dual-task performance and potentially reduce fall risks among older adults. • Older age is negatively associated with static balance tested with a portable force plate. • Older age is negatively associated with gait velocity and stride length during a functional task. • Adding a cognitive dual task is associated with declines in gait velocity, cadence and stride length. • The cost of adding a dual task was similar for younger and older adults. • Weak to moderate correlations were found between static balance and gait parameters.